2019
DOI: 10.1080/2162402x.2019.1648170
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional tumor-reactive T cells are effectively expanded from non-small cell lung cancers, and correlate with an immune-engaged T cell profile

Abstract: Non-small cell lung cancer (NSCLC) is the second most prevalent type of cancer. With the current treatment regimens, the mortality rate remains high. Therefore, better therapeutic approaches are necessary. NSCLCs generally possess many genetic mutations and are well infiltrated by T cells (TIL), making TIL therapy an attractive option. Here we show that T cells from treatment naive, stage I-IVa NSCLC tumors can effectively be isolated and expanded, with similar efficiency as from normal lung tissue. Importantl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 47 publications
(71 reference statements)
6
54
1
Order By: Relevance
“… 42 , 54 Similarly, 76% of our NSCLC-derived TIL products showed tumor-specific cytokine responses to autologous tumors, of which 25% was even polyfunctional. 21 Thus, the restricted tumor-specific cytokine production we observed for RCC-derived TIL products is tumor-type specific. The relative absence of tumor-specific cytokine production could not be attributed to an overall inability to produce these cytokines, as the RCC TILs produced ample amounts upon stimulation with PMA/ionomycin.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“… 42 , 54 Similarly, 76% of our NSCLC-derived TIL products showed tumor-specific cytokine responses to autologous tumors, of which 25% was even polyfunctional. 21 Thus, the restricted tumor-specific cytokine production we observed for RCC-derived TIL products is tumor-type specific. The relative absence of tumor-specific cytokine production could not be attributed to an overall inability to produce these cytokines, as the RCC TILs produced ample amounts upon stimulation with PMA/ionomycin.…”
Section: Discussionmentioning
confidence: 79%
“…These percentages of FOXP3 + T cells are substantially lower than those measured in melanoma or ovarian cancer lesions (~15% of CD3 + T cells). 21 …”
Section: Resultsmentioning
confidence: 99%
“…CD4 + enriched cells grown in the enhanced cytokine conditions also produced a statistically significant increase of IL-17A-producing CD4 + T cells ( Figure 2E ). Additionally, MCPyV TAg-specific cells gated on CD3 + CD4 + TNFα + cells were polyfunctional for IL-2 and the Th1 effector molecules granzyme B, IFNγ, and TNFα ( Figure 2F ), a feature associated with immune-mediated tumor clearance ( 28 , 29 ). Cytotoxicity assays demonstrated that expanded MCPyV TAg-specific T cells do not induce killing of peptide pulsed autologous moDCs or phytohemagglutinin induced blasts (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The downloaded RNA-seq data from HNSCC tumor biopsies were uploaded onto CIBERSORT (https://cibersort.stanford.edu/index.php). CIBERSORT input the RNA-seq data into a matrix of reference gene expression signatures (LM22), which contains 547 genes that distinguish phenotypes of 22 human hematopoietic cell [31,32]. This output was used to estimate the relative proportions of the immune cell type composition of a tumor biopsy.…”
Section: Analysis Of Patient Samples Obtained By Tcgamentioning
confidence: 99%